Hysteretic Behavior in Voltage-Gated Channels - Villalba-Galea, Carlos A.; Chiem, Alvin T. (Frontiers in Pharmacology, 2020)
An ever-growing body of evidence has started to show that voltage-gated ion channels are likely systems displaying hysteresis. This phenomenon has been observed in the form of dynamic changes in voltage dependence of channel activity and in the deactivation kinetic. This review offers quick perspective of what hysteresis is voltage-gated channels is and their potential physiological relevance.